An evaluation of the MEDLINE database of U.P. Manila Medical Library its coverage and usage - Delgado, Emelorna C. Esteban (2005)
MEDLINE has long been appreciated as a major resource for those with academic or research questions. More recently, it has been recognized that MEDLINE supports informed clinical practice as well. A number of published studies report that MEDLINE literature searches have a significant positive effect on clinical problem-solving and patient outcomes.